Effect of soybean on subsequent maize grain yield in the Guinea savanna zone of West Africa - Carsky, R.J.; Abaidoo, Robert C.; Dashiell, Kenton E.; Sanginga, N. (African Journals Online, 1997)
Two varieties of soybean (Glycine max (L.) Merr.) and a maize (Zea mays L.) control crop were grown in replicated trials at 10 sites in the Guinea savana of Nigeria in 1993 followed by a test crop of maize in 1994 with 20 or 60 kg N ha-1 to test effect of soybean on subsequent maize grain yield. Maize grain yield increase following soybean was variable but the main effect of previous soybean crop was positive even though the soybean was not inoculated with rhizobia and the aboveground soybean residues, except litter fallen before harvest, were exported from the fields, following the present farmer practice. The yield increase following the medium duration soybean variety (TGx1660-19F) was similar to that from 40 kg N ha-1 applied 4 weeks after planting to maize preceded by maize. The increase following the early soybean variety (TGx1456-2E) was significantly (P<0.05) smaller than that following the medium duration soybean variety. Total N in the 0 to 10 cm depth of the previous TGx1660-19F plots (0.063%) was significantly greater (P<0.05) than in the previous maize plots (0.058%) when analysed for the combined sites. Thus, the effect of previous soybean crop on maize grain yield was due mostly to residual N availability. Additional research is justified to estimate how soybean crop management influences the yield of subsequent maize in the savanna zone.